2011
DOI: 10.1007/s10336-011-0754-6
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of extra-pair paternity or intraspecific brood parasitism in the Imperial Shag Phalacrocorax atriceps

Abstract: In long-lived birds with significant paternal care contribution, as the case of seabirds, extra-pair paternity (EPP) is an infrequent phenomenon. Intriguingly, and in contrast to the general pattern exhibited by seabirds, EPP rates appear relatively high in the two species of cormorants and shags (Phalacrocoracidae family) analyzed so far. We test for EPP in the Imperial Shag Phalacrocorax atriceps, a medium-sized colonial seabird, using four DNA microsatellites originally developed for Great Cormorants P. car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the analysis, the error rate of genotyping was set to 0.025 as suggested by Wang ( 2004 ). We did not allow for multiple maternity within broods, as despite a large body of molecular paternity studies in Phalacrocorax genus and other genera from Suliformes order (Graves et al 1993 ; Baumgarten et al 2001 ; Dearborn et al 2001 ; Anderson and Boag 2006 ; Baião and Parker 2009 ; Calderón et al 2012 ), no sound empirical evidence was found for either conspecific brood parasitism or quasi parasitism in this group of birds (reviewed in Yom-Tov 2001 ; Griffith et al 2004 ). Secondly, we tested for full-sibling relationships using likelihood ratio tests based on Queller and Goodnight’s r (Queller and Goodnight 1989 ; Goodnight and Queller 1999 ) implemented in KINGROUP v2 (Konovalov et al 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the analysis, the error rate of genotyping was set to 0.025 as suggested by Wang ( 2004 ). We did not allow for multiple maternity within broods, as despite a large body of molecular paternity studies in Phalacrocorax genus and other genera from Suliformes order (Graves et al 1993 ; Baumgarten et al 2001 ; Dearborn et al 2001 ; Anderson and Boag 2006 ; Baião and Parker 2009 ; Calderón et al 2012 ), no sound empirical evidence was found for either conspecific brood parasitism or quasi parasitism in this group of birds (reviewed in Yom-Tov 2001 ; Griffith et al 2004 ). Secondly, we tested for full-sibling relationships using likelihood ratio tests based on Queller and Goodnight’s r (Queller and Goodnight 1989 ; Goodnight and Queller 1999 ) implemented in KINGROUP v2 (Konovalov et al 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Imperial Shag is a colonial ground-nesting seabird where both parents play an active role in the care and feeding of chicks throughout the breeding cycle ( Johnsgard, 1993 ). This monogamous seabird usually lays a three-egg clutch that hatches asynchronously over 4–5 days ( Svagelj and Quintana, 2011a , Svagelj and Quintana, 2011b , Calderón et al., 2012 ). This hatching pattern results in age and size asymmetry between chicks, where the probability of fledging drastically decreases with hatching order ( Svagelj and Quintana, 2011a ).…”
Section: Introductionmentioning
confidence: 99%
“…One such strategy is nest parasitism, in which the costs of parental investment are transferred to other individuals. However, anti-parasitic strategies of hosts may end up counterbalancing the extra benefits that a parasite can derive in not caring for their own offspring (Lezalová-Piálková 2011, Calderón et al 2012). In species characterized by alloparental care, there is a division in the costs of caring for offspring among individuals that breed in close proximity to one another or that have a level of kinship that justifies their investment through increased inclusive fitness.…”
Section: Introductionmentioning
confidence: 99%